Factor XI inhibitors: what should clinicians know. (30th March 2023) - Pandey, Arjun; Verma, Raj; Eikelboom, John; Verma, Subodh
Abstract : Purpose of review: Factor XI (FXI) inhibitors were developed to address unmet needs and limitations of current anticoagulants and are currently being studied in several indications. In this paper, we review the rationale for the development of these agents and summarize what clinicians should know about drugs that target FXI. Recent findings: Patients with FXI deficiency may have a lower risk of venous thromboembolism and cardiovascular events and have a variable but generally mild bleeding diathesis. FXI has been proposed as a target for anticoagulants due to the potential for reduction in thrombosis with a lower risk of bleeding than current anticoagulant agents. Several classes of drugs that target FXI are under development, of which three classes (small molecule inhibitors, antisense oligonucleotides and monoclonal antibodies) have been studied in Phase II trials. At least three large Phase III trial programs are planned or are underway, and will study the efficacy and safety of FXI inhibitors in tens of thousands of patients across a variety of indications including atrial fibrillation, stroke and cancer-associated venous thromboembolism. Summary: FXI inhibitors were developed with the hope of attenuating thrombosis with reduced bleeding/impairment of haemostasis. These agents have shown promise in preliminary trials with a low rate of bleeding. Ongoing Phase III investigations will inform the utility of these agents in clinical practice.